Syntropia – acid-dependent diseases and hypertension (One Health & Risk Management, 2022)
Introduction. With syntropy of CVD and AH, the pathology of the digestive system can exacerbate the course of AH and develop special conditions for increasing the risk of cardiovascular complications. Pharmacotherapy of HD may affect the course and progression of gastroesophageal reflux disease.Material and methods. The study was conducted using the PubMed, Z-library, NCIB, Medscape, Mendeley databases using the keywords: “syntropy”, “comorbidity”, “arterial hypertension”, “acid-dependent diseases”, “gastric ulcer”, “gastroesophageal reflux disease”.Results. AH and CVD are quite often observed together, having, moreover, a conditioned commonality of the mechanisms of formation. The proximity of the location with the heart, the commonality of innervation, in the pathology of the esophagus, can create viscero-visceral reflexes and provoke arrhythmias, imitate coronary heart disease. Pathology of the upper gastrointestinal tract can lead to functional disorders of the cardiovascular system, manifested through the autonomic nervous system. The combined course of AH and CVD, observed, according to various sources, from 11.6% to 50%, is not just random, but may have pathogenetic and etiological patterns. Comorbidity of CVD and AH can enhance the development of the main pathological process and lead to disruption of adaptive mechanisms.Conclusions. The syntropy of AH and CVD requires thorough scientific studies to discover and elucidate the pathogenetic features of the course and methods of better drug therapy.
Keywords: syntropy; comorbidity; arterial hypertension; gastroesophageal reflux disease